2008
DOI: 10.1042/bj20071562
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of free complex-type N-glycans in MKN7 and MKN45 stomach cancer cells

Abstract: During the N-glycosylation reaction, it has been shown that 'free' N-glycans are generated either from lipid-linked oligosaccharides or from misfolded glycoproteins. In both cases, occurrence of high mannose-type free glycans is well-documented, and the molecular mechanism for their catabolism in the cytosol has been studied. On the other hand, little, if anything, is known with regard to the accumulation of more processed, complex-type free oligosaccharides in the cytosol of mammalian cells. During the course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 55 publications
4
41
0
Order By: Relevance
“…The cytosolic sialidase Neu2 is known to catabolize cytosolic sialyl-fOSs (13). We confirmed by quantitative PCR that Neu2 expression is, if it exists at all, very low in both WT cells and Atg5 Ϫ/Ϫ MEF cells (data not shown).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The cytosolic sialidase Neu2 is known to catabolize cytosolic sialyl-fOSs (13). We confirmed by quantitative PCR that Neu2 expression is, if it exists at all, very low in both WT cells and Atg5 Ϫ/Ϫ MEF cells (data not shown).…”
Section: Discussionsupporting
confidence: 66%
“…There are few reports on the occurrence of sialyl-fOSs in the cytosol of mammalian cells (12,13). Most recent studies, however, have shown that similar sialyl-fOSs are accumulated in human pancreatic (33) or prostate cancers (34) but not in normal epithelial cells, thus suggesting that these glycans can serve as useful tumor markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This glycan was previously observed in gastric adenocarcinoma cells, and combined studies using MS/MS and sequential digestions with specific glycosidases confirmed that the Man 1-6 arm was removed to form a characteristic biantennary glycan. 51 Nontypical oligosaccharide peaks which were detected at m/z 1103.4 and 1265.4 (Figure 3a) produced MS/MS fragmentation patterns consistent with Hex 6 PHN and Hex 7 PHN compositions. These neutral oligosaccharides were found in all CEM cell line samples and their presence is suspected to be as a result of culturing cells in medium rather than expression in cancer cells.…”
Section: Maldi-ms Analysis Of N-glycans From Mcf-7 and Cemmentioning
confidence: 99%
“…Of course, it should be noted that the scheme presented in Fig. 2 is only for high-mannosetype glycans, and degradation pathway for complex type free glycans, which are also reported in the cytosol of mammalian cells and tissues (37,38), is very poorly understood. Moreover, I frankly wonder if anyone has ever seriously examined whether there is any non-lysosomal degradation pathway for other type of glycans, such as mucintype O-glycans (exception is the recent paper by Dr. Ito's group about theˆnding of neutral b-glycosylceramidase, which could be involved in a novel nonlysosomal catabolic pathway of glucosylceramide (39)).…”
Section: E Other Unanswered Questionsmentioning
confidence: 99%